Macrostructural Narrative Language of Adolescents and Young Adults with Down Syndrome or Fragile X Syndrome - Finestack, Lizbeth H. (2011)
PURPOSE: To gain a better understanding of language abilities, the expressive macrostructural narrative language abilities of verbally expressive adolescents and young adults with Down syndrome (DS) and those with fragile X syndrome (FXS) were examined. METHOD: The authors evaluated 24 adolescents and young adults with DS, 12 male adolescents and young adults with FXS, and 21 younger children with typical development (TD). Narrative samples were assessed at the macrostructural level using the Narrative Scoring Scheme (NSS; Heilmann, Miller, Nockerts, & Dunaway, 2010). Three group comparisons were made using: (a) the full sample matched on nonverbal mental age, (b) a subset of the participants individually matched on nonverbal mental age, and (c) a subset of participants individually matched on mean length of utterance. RESULTS: Study analyses revealed that the DS and FXS groups significantly outperformed the TD group on a limited number of NSS measures. No significant differences emerged between the DS and FXS groups. CONCLUSIONS: Study results suggest that some aspects of macrostructural narrative language may be relative strengths for adolescents and young adults with DS and those with FXS. These results can be used to create a more nuanced and informed approach to assessment and intervention for these populations.